Hydropower operation in a changing market environment: A Swiss case study - Moritz Schillinger; Hannes Weigt; Michael Barry; René Schumann (University of Basel, Center of Business and Economics (WWZ), 2017)
Hydropower (HP) is expected to play an important role in the European energy transition by providing back-up and storage capacity as well as flexibility for intermittent renewable energies. However, due to low electricity market prices the profitability of HP decreased in recent years. In this paper, we analyze historic revenue potentials and future market prospects for HP taking into account different development paths. Using a short-term HP operation model to capture market opportunities as well as technical and natural constraints of HP plants, we model three representative Swiss HP plants. The results indicate that in the last years, balancing markets could have provided significant additional revenues for HP plants. However, accounting for uncertainties and market characteristics, the potential of balancing markets is reduced but cross-market optimization is still beneficial. Looking into the future, market price prospects for the coming decade are low to modest. Global fuel markets and the European Union Emissions Trading System (ETS) will be the main drivers for decisions for Swiss HP. The revenue potential from balancing markets will be reduced significantly in the future if all Swiss HP operators aim for balancing. While optimized operation across markets helps Swiss HP to increase its revenues, it is limited in scale.
Keywords: 330; hydropower; cross-market optimization; balancing; Switzerland